PERLINDUNGAN HAK KEAMANAN DATA PRIBADI KONSUMEN PINJAMAN ONLINE DANA CAIR - Aqilah Nurshafira Anwar; N.G.N. Renti Maharaini Kerti (Fakultas Hukum Universitas Trisakti, 2022)
Regulations for online loans have been put in place to keep things in order and safeguard consumers from unforeseen events, yet in reality personal data exploitation still happens among instant cash customers. How are the Financial Services Authority's efforts as a supervisor in dealing with misuse of consumer personal data as a method of billing in instant cash online loan services? The problem is whether consumer protection regulations related to online loan services have provided protection for personal data security rights in the method of billing consumers on instant cash online loans. This study's methodology is normative, descriptive in nature, with primary and secondary sources of information used to support a qualitative analysis and forming judgments through deductive reasoning. Research findings, analysis, and conclusions The restrictions in place in Indonesia have been able to protect instant cash online loan borrowers, but in practice corporate actors continue to break the law and the general public is not well-informed about using online lending services. Through the publication of lists of illegal online loans and submission of application blocks to the Ministry of Communication and Information, OJK and SWI have worked together to combat illegal online loans that could harm the public.